Perspectives on the Application of Supercritical Antisolvent Fractionation Process for the Purification of Plant Extracts: Effects of Operating Parameters and Patent Survey - R.C. Torres, Abel; L. Santana, æ#129;dina; T. Santos, Diego; Angela A. Meireles, M. (Recent Patents on Engineering, 2016)
Background: A recently developed process entitled Supercritical Antisolvent Fractionation (SAF) was recently described for the fractionation of plant extract solutions using supercritical fluids to give two or more fractions containing bioactive compounds with widely differing polarities. An updated overview of SAF of natural products is presented in this article. Objective: The goal of this work is to show some perspectives about the use of supercritical CO2 (SC-CO2) applied to the fractionation of plant extract compounds, such as phenolic compounds, lipids, and carotenoids; among other components, those extracted from seeds, leaves, stems, roots and other parts of the plants are described. The main features and mechanisms of antisolvent techniques that contribute to the understanding of the fundamentals of the supercritical antisolvent fractionation (SAF) process are also described. Method: The influence of various operating parameters, such as, CO2 temperature and pressure, CO2 flow rate, among others, during SAF process on the purification efficiency and particle morphology and the main differences about the patented SAF processes are reviewed. Results: The various experimental works intend to optimize their processes through adaptations or modifications of equipments that constitute the SAF unit, as the study of process parameters. Conclusion: SAF process is a technique to produce particles with high yield and purity of bioactive compounds. On the other hand, patents developed using this type of process are very scarce, less attention being given be given to the potential of this technique to purify plant extracts with a very complex content of bioactive compounds.
Keywords: Fractionation methods